SOP for quantification of total phytates in beans, rice, and maize flour - Orozco Agredo, Juan Camilo; Taleon, Victor; Patiño Lenis, Gelver; Gallego Castillo, Sonia (2024)
This SOP describes the stages involved in the treatment process of the grain samples to be analyzed (beans, maize, and rice) to subsequently quantify the total phytate content by spectrophotometry